If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -6x + -7 = x + 2 Reorder the terms: 8 + -7 + -6x = x + 2 Combine like terms: 8 + -7 = 1 1 + -6x = x + 2 Reorder the terms: 1 + -6x = 2 + x Solving 1 + -6x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -6x + -1x = 2 + x + -1x Combine like terms: -6x + -1x = -7x 1 + -7x = 2 + x + -1x Combine like terms: x + -1x = 0 1 + -7x = 2 + 0 1 + -7x = 2 Add '-1' to each side of the equation. 1 + -1 + -7x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = 2 + -1 -7x = 2 + -1 Combine like terms: 2 + -1 = 1 -7x = 1 Divide each side by '-7'. x = -0.1428571429 Simplifying x = -0.1428571429
| x+(x+3-9)= | | x(4x+7)-(4x^2+5x+4)=4 | | 5000*0.04= | | y=(x+2)(3x-10) | | -147-9x=93-42x | | 12-5q=q+3 | | y=-(x-1)*-12 | | (4*1)2=6 | | 5x-8=x+2 | | 5(-2x-8)=6(-2x-3) | | 20-m=9 | | y=-22+6 | | 2k-2=-2-6k | | 8-7a=-1a-16 | | x-12+12+2x=27 | | 6(x+4)-(6x+24)=12 | | (4*1)2=16 | | 6x-7=25 | | 143-5x=14-8x | | 8-2b=-.6(12b+6) | | 4x+36=14x-84 | | 170+.25x=310 | | X^2+1.5x+1.25=0 | | 8(x+10)+x=98 | | -1=8x+5 | | 9a+10= | | 4n-2=d | | 25z*2=81 | | 16y*2=36 | | 5(12x-9)=60x-1 | | -2=3z+4 | | 2*2+5x=3 |